Current situation in Polish nuclear medicine and Polish example of model Nuclear Medicine Centre meeting European Union requirements - Lica, Jan Jakub; Grabe, Grzegorz Jan; Bandurski, Tomasz (European Journal of Oncology and Environmental Health, 2016)
Nuclear medicine is currently a well-established part of medicine. It is applied in many fields of clinical medicine and science like endocrinology, oncology, cardiology, molecular medicine and engineering, radiopharmacy, physics and information science. Due to its increasing importance and application, several regulation and supervision bodies have been founded to ensure safe usage of radiation and to improve diagnostic and therapeutic procedures. This article reviews the legal requirements of Polish law regarding a fully functional Nuclear Medicine Centre (NMC) and reports on the current situation of nuclear medicine in Poland. It also suggests a model project for NMCs compatible with Polish and European Union regulations.